UNLOCKING CREATIVITY IN CHINESE SMES: THE ROLE OF GENERATION Y LEADERSHIP AND TEAM DYNAMICS - LAN, Jing; Chienwattanasook, Krisada (Asian Administration and Management Review, 2025)
This study explores the influence of leadership role efficacy, team identification, team trust, and team entrepreneurial orientation on the team creativity of Generation Y entrepreneurs in Chinese SMEs. Analyzing responses from 604 SME entrepreneurs across various sectors using PLS-SEM, the results indicate that team entrepreneurial orientation, identification, leadership role efficacy, and trust significantly impact team creativity. Team entrepreneurial orientation exerted the most decisive influence, followed by team identification, leadership role efficacy, and team trust. Therefore, SME managers should foster entrepreneurial team dynamics by cultivating a shared vision, aligning team goals, and creating an open space. The leadership skills of team leaders should be improved to increase self-confidence in their role and foster a culture of trust. These findings contribute to understanding leadership and team dynamics in promoting creativity within Chinese SMEs, providing implications for policy initiatives and management practices.